## Ratio of the area of a square to the area of a triangle

Simplificatation, evaluation, linear equations, linear graphs, linear inequalities, basic word problems, etc.
kevin
Posts: 2
Joined: Thu Jul 07, 2011 5:58 am
Contact:

### Ratio of the area of a square to the area of a triangle

What is the ratio of the area of a square of side 5 to an equilateral triangle with sides of 5? Doesn't seem like a hard question, but the given answer is 4sqrt(3)/3.

Any ideas on how to get to this final answer?

Thanks

little_dragon
Posts: 226
Joined: Mon Dec 08, 2008 5:18 pm
Contact:

### Re: Ratio of the area of a square to the area of a triangle

What is the ratio of the area of a square of side 5 to an equilateral triangle with sides of 5? Doesn't seem like a hard question, but the given answer is 4sqrt(3)/3.
wat areas did U get? wat did U get when U divided?

kevin
Posts: 2
Joined: Thu Jul 07, 2011 5:58 am
Contact:

### Re: Ratio of the area of a square to the area of a triangle

I got 25 for the area of the square and the triangle I got 6.25

maggiemagnet
Posts: 358
Joined: Mon Dec 08, 2008 12:32 am
Contact:

### Re: Ratio of the area of a square to the area of a triangle

I got 25 for the area of the square and the triangle I got 6.25
You shouldn't have gotten an exact decimal value for the triangle, so something went wrong there. Please reply showing your steps, starting with finding the altitude of the equilateral triangle (possibly using the ratios for a 30-60-90 triangle, which is half of an equilateral). Thanks!

monkeyolsen
Posts: 1
Joined: Sat Jul 09, 2011 4:18 pm
Contact:

### Re: Ratio of the area of a square to the area of a triangle

area of square = 5*5 = 25

Triangle

altitude:
let the altitude of the equilateral triangle be x
5^2 = (2.5)^2 + x^2
x^2 = 25-(25/4)
= 75/4
x = 5root(3)/2

area of triangle = (b*h)/2
b = 5
h= x = 5root(3)/2

area = [(5)*(5root(3)/2)]/2
= 25root(3)/4

ratio of area of square to area of triangle = 25/[25root(3)/4]
= [25*4]/[25 root(3)] = 4/[root(3)]

multiply top and bottom by [root(3)]
4*root(3)/[root(3)*root(3)] = 4root(3)/3